Memory, gender and political repression in the Southern Cone (1984-1991) (Tempo e Argumento, 2010)
This article examines, from a gender perspective, the reports on human rights violations, known as Nunca Más, written at the time of transition from military dictatorship to democracy in Argentina (1984), Brazil (1985), Uruguay (1989) and Chile (1991). The Nunca más, despite the different conditions in which they have been developed, remained in their respective countries as interpretative frameworks of the past dictatorship, an "iconic memory", extensively documented and settled on a concern for accuracy. The analysis of those reports is made focusing on possible gender differences of political repression.
Keywords: military dictatorship; political repression; torture; Southern Cone